Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2008)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2008_10
Keywords: MF648; Economics; Crops; MF